Akses Informasi Pemustaka Tunanetra Pada Layanan Koleksi Braille Corner Di Dinas Perpustakaan Dan Arsip Daerah Kota Malang - Mafatihul Salma; Galuh Indah Zatadini (UIN Mataram, 2025)
This study aims to examine the information access process for visually impaired library users at the Braille Corner of the Malang City Library and Archives Office. The information- seeking model used is a combination of approaches by Ellis and Kuhlthau and Wilson, which outlines the stages of information-seeking from uncertainty to understanding. The research findings show that visually impaired users visit Braille Corner for various reasons, such as looking for books or simply the desire to read. In the initial stage, they recognize the need for information and begin searching by utilizing various facilities such as Braille books, smart computers, and talking books. If the information they seek is not found, they tend to ask the librarian or request recommendations for other collections. The information-seeking process involves filtering and selecting relevant information, with further interaction between the users and librarians to verify the accuracy of the information. Users express satisfaction and comfort with the services provided, although sometimes physical and psychological conditions can affect their mood when accessing information. However, librarians face challenges related to infrastructure and facilities that are not yet fully disability-friendly, as well as the need for training for new librarians. This study concludes that although users are satisfied with the facilities and services, there are still several challenges related to infrastructure and human resource development that need to be addressed to improve the quality of information services for visually impaired users at Braille Corner, Malang City Library.